1990
DOI: 10.1002/glia.440030305
|View full text |Cite
|
Sign up to set email alerts
|

Comparative immunohistochemical study of glial filament proteins (glial fibrillary acidic protein and vimentin) in goldfish, octopus, and snail

Abstract: Glial fibrillary acidic protein (GFAP) and vimentin proteins are known to be component proteins of glial filaments in the CNS of many vertebrates. The nature of the filaments present in the glial cells of the goldfish optic tectum and in the CNS of two members of the Mollusca (Helix pomatia and Octopus vulgaris) were investigated using immunocytochemical localization of monoclonal antibodies to GFAP and vimentin. Immunoblots visualized by the alkaline phosphatase method showed cross-reactive protein bands to G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
2
2

Year Published

1993
1993
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 54 publications
3
49
2
2
Order By: Relevance
“…Nevertheless vimentin is still expressed in the ependymal cells of some regions of adult CNS in mammals (Chouaf et al 1989 ;Oudega & Marani, 1991 ;Yamada et al 1992), birds (Alvarez-Buylla et al 1987 ;Kalman et al 1998), reptiles (Lauro et al 1991 ; present study), amphibians (Zamora & Mutin, 1988 ;Lauro et al 1991 ;Lazzari et al 1997) and fish (Cardone & Roots, 1990 ;Rubio et al 1992 ;Bodega et al 1993).…”
Section: mentioning
confidence: 57%
See 1 more Smart Citation
“…Nevertheless vimentin is still expressed in the ependymal cells of some regions of adult CNS in mammals (Chouaf et al 1989 ;Oudega & Marani, 1991 ;Yamada et al 1992), birds (Alvarez-Buylla et al 1987 ;Kalman et al 1998), reptiles (Lauro et al 1991 ; present study), amphibians (Zamora & Mutin, 1988 ;Lauro et al 1991 ;Lazzari et al 1997) and fish (Cardone & Roots, 1990 ;Rubio et al 1992 ;Bodega et al 1993).…”
Section: mentioning
confidence: 57%
“…Even though vimentin has been found in immature cells of the astroglial lineage in mammals (Elmquist et al 1994 ;Pulido-Caballero et al 1994) and reptiles (Monzon-Mayor et al 1990 ;Yanes et al 1990), it is still present in adult glial cells in teleosts and amphibians (Zamora & Mutin, 1988 ;Cardone & Roots, 1990 ;Rubio et al 1992 ;Lazzari et al 1997). Furthermore, vimentin is highly conserved in phylogenesis as suggested by the cross reaction of antibodies produced against mammalian vimentin with the corresponding protein in birds and amphibians (Bennett et al 1978 ;Szaro & Gainer, 1988 ;Zamora & Mutin, 1988 ;Bodega et al 1994).…”
mentioning
confidence: 99%
“…Accordingly, GFAP-like immunoreactivity has been shown in enteric glia (Jessen and Mirsky, 1980), Schwann cells of unmyelinated peripheral nerve fibers (Yen and Fields, 1981;Dahl et al, 1982), lens epithelium (Hatfield et al, 1984), and Kupffer cells in the liver (Gard et al, 1985), among others. Filaments of morphological structure similar to the intermediate glial filament have been reported in the glial cells of many mammals, birds, reptiles, fishes (Dahl et al, 1985), and in some invertebrates such as annelids and mollusks (see Radojcic and Pentreath, 1979;Cardone and Roots, 1990;Riehl and Schlue, 1998;Dos Santos et al, 2002).…”
Section: Introductionmentioning
confidence: 84%
“…Because of the main role that has been attributed to GFAP in astrocytes, as a cytoskeleton stabilizer (see Rutka et al, 1997), and to the presence of this protein in few invertebrates (see Radojcic and Pentreath, 1979;Cardone and Roots, 1990, Riehl and Schlue, 1998, Dos Santos et al, 2002, we wanted to search for the presence of GFAP-like proteins in crustaceans.…”
Section: Introductionmentioning
confidence: 99%
“…These cells have been classically studied with metallic impregnation (see Lara et al, 1995) and electron microscopy Maxwell, 1966, 1967;Tapp, 1973;Laufer and Vanegas, 1974;Peter and Nagahama, 1976;Roots, 1978;Stevenson and Yoon, 1982;Díaz-Regueira et al, 1993). Immunocytochemical studies of ependymal and radial glia cells of bony fishes reported the presence of both GFAP (Onteniente et al, 1983;Anderson et al, 1984;Raamsdonk et al, 1984;Dahl et al, 1985;Levine, 1989;Nona et al, 1989;Cardone and Roots, 1990;Rubio et al, 1992;Díaz-Regueira et al, 1993;Ká lmá n, 1998;Kawai et al, 2001; Ká lmá n and Ari, 2002) and Vim (Cardone and Roots, 1990;Rubio et al, 1992;Díaz-Regueira et al, 1993;De Guevara et al, 1994;Cerdà et al, 1998). By using NADPH-diaphorase histochemistry, Ma (1993) described the regional distribution of tanycytes in the adult brain of the sunfish (Lepomis sp.).…”
mentioning
confidence: 97%